Economic Performance and Women Entrepreneurs in Nigeria - Nwokoro, Ngozi A. (Research Parks Publishers, 2022)
For a country to achieve its development goals, women must be incorporated in the entrepreneurship activities. A lot of literature supports the role of women in economic development. This study seeks to examine factors influencing the performance of women entrepreneurs in Lagos state. The target population for this research included all the 12.300 women entrepreneurs in Surulere, Ikorodu, Agege and Eti-Osa, with a sample size of 370 determined from Krejcie and Morgan table and randomly selected. A descriptive Research design was used to allow the researcher to gather information, summarize, present and interpret data for the purpose of clarification. Stratified random sampling was used where each location formed strata. Proportional allocation was used to compute the exact number of subjects in each location which was a correct representation from the strata. The received data was classified, summarized, coded, sorted and SPSS and excel softwares used in analysis. From this study, it was observed that although there is the possibility of women entrepreneurs operating business enterprises in the same capacity and magnitude as men, traditional roles and practices such as domestic commitments, low levels of education, lack of property ownership and lack of opportunity driven motive to start enterprises continues to influence the performance of women entrepreneurs negatively in terms of monthly income sales, profit margin and types of business enterprise.